COMPUTATIONAL MUTAGENESIS STUDY OF BACILLUS AQUIMARIS MKSC 6.2 ?-AMYLASE ON SURFACE BINDING SITE RESIDUE TYR400 - Claudia Tan, Josephine
BaqA, ?-amylase produced from Bacillus aquimaris MKSC 6.2. is known to degrade raw starch granules. BaqA tertiary structure model lacks any starch-binding domains commonly found in grain degrading enzymes. Residues that play roles in the active side of BaqA are the catalytic triad (Asp246, Arg247, and Asp248) in domain A. In addition, BaqA also has 2 binding sides of the substrate, namely two adjacent tryptophan residues (Trp201 and Trp202) in domain A and sugar tong residue (Tyr400) in the C domain. In this study, BaqA?C was particularly used, which is the truncated version of BaqA in the C-terminal in order to increase hydrolysis activity of starch solution. This study aims for deeper understanding of Tyr400 role in predicted ‘sugar tongs’ surface binding site (SBS) through in silico mutational study of BaqA?C Y400W and BaqA?C Y400S variants. Computational analysis was conducted through molecular docking and molecular dynamics (MD) methods to observe the effect of mutation on Tyr400. Docking score obtained by molecular docking did not show any significant difference, but molecular docking simulation shows that Tyr400 in BaqA?C had managed to maintain the bond with acarbose much longer than both mutations Y400W and Y400S. Therefore, Tyr400 does play a role in maintaining affinity of substrate in the ‘sugar tongs’ SBS. Single residue substitution Tyr400 into tryptophan and serine residues both reduces protein stability. Hence, it is possible that Tyr400 is an important residue in maintaining protein stability. Glu401 might also contribute in retaining substrate on the ’sugar tongs’ SBS through hydrogen bonds.